2009
DOI: 10.4102/curationis.v32i3.1224
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of primary health care nurses in implementing integrated management of childhood illnesses strategy at selected clinics of Limpopo Province

Abstract: Treatment of the under five years is a national priority as an attempt in curbing deaths and deformities affecting children. Primary health care was implemented in the clinics in order to help in the treatment of illnesses affecting the community, including children. As a result of childhood illnesses; the World Health Organization (WHO) and United Nation Children's Fund (UNICEF) came up with Integrated Management of Childhood illnesses (IMCI) strategy to enhance treatment of such illnesses in developing count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 3 publications
4
11
0
Order By: Relevance
“…This was inconsistent with other studies, for instance study conducted in Indonesia and Tanzania [15][16].This difference might be due to difference in economic status, study area and study period. However, this finding is consistent with other several similar studies carried out in Africa [9,18,[20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was inconsistent with other studies, for instance study conducted in Indonesia and Tanzania [15][16].This difference might be due to difference in economic status, study area and study period. However, this finding is consistent with other several similar studies carried out in Africa [9,18,[20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 93%
“…Health system related factor ,which composed the factors like lack of supplies ,lack of supervision, frequent unavailability of IMNCI drugs and chart booklets, inadequate facility support were also listed by nurses as the others factors affecting utilization of IMNCI guidelines and this finding was also supported by another several comparable study conducted in different parts of the world [18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 74%
“…These studies found that some of the IMCI recommendations are not carried out because of insufficient support from the government and stakeholders. Vhuromu & Davhana-Maselesele [30] explored the experiences of HCWs in South Africa, highlighting the lack of human and material resources as one of the reasons that hampered the implementation of IMCI services in Limpopo province. Because of problems with shortages of medication, HCWs said there were instances that they referred patients to nearby hospitals just to get medications, even if it was not otherwise necessary.…”
Section: Resourcesmentioning
confidence: 99%
“…As an intervention that is well accepted cannot afford logistic breakdowns, the nature of distribution within the system needs to be improved. Other studies report that frequent unavailability of necessary equipment can have negative impact on motivation and performance of health workers [42-44]. To keep the motivation of the health staff towards the FD at high levels, an unavailability of ITNs must be avoided.…”
Section: Discussionmentioning
confidence: 99%